The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1111/apha.12767
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia exposure and B‐type natriuretic peptide release from Langendorff heart of rats

Abstract: AimWe studied whether available oxygen without induced mechanical stretch regulates the release of the biologically active B‐type natriuretic peptide (BNP) from Langendorff heart.MethodsRat hearts were isolated and perfused with a physiological Krebs–Henseleit solution at a constant hydrostatic pressure in Langendorff set‐up. The basal O2 level of perfusate (24.4 ± 0.04 mg L−1) was gradually lowered to 3.0 ± 0.01 mg L−1 over 20 min using N2 gas (n = 7). BNP and O2 level were measured from coronary flow. During… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 46 publications
1
8
0
Order By: Relevance
“…The aorta was swiftly cannulated with a 21-gage cannula and the heart was retroactively perfused with Tyrode Solution (137 mM NaCl, 5.4 mM KCl, 1.2 mM MgCl 2 , 10 mM HEPES, 10 mM glucose, 1.2 mM NaH 2 PO 4 , and 1.2 mM CaCl 2 ) aerated with a mixture of O 2 (95%) and CO 2 (5%) in order to maintain O 2 levels at 800 nmol/mL using a murine Langendorff perfusion apparatus. After a stabilization period of 20 min, the perfusion buffer was switched to the Tyrode Solutions containing various O 2 concentrations (normoxia: 800 nmol/mL; mild hypoxia: 550 nmol/mL; heavy hypoxia: 300 nmol/mL), which have been proven to induce various myocardial injuries in previous studies (Anttila et al, 2017) for an additional 40 min of perfusion. Then, the hearts were cut into small pieces and homogenized in cold isolation buffer (20 mM HEPES, 220 mM mannitol, 68 mM sucrose, 80 mM KCl, 0.5 mM EGTA, 2 mM magnesium acetate, supplemented with protease inhibitors, pH 7.4) for mitochondrial isolation which was done using a protocol adapted from a previous study (McLelland et al, 2016).…”
Section: Isolation Of Mitochondria and Reconstitution Of MDV In Vitromentioning
confidence: 99%
“…The aorta was swiftly cannulated with a 21-gage cannula and the heart was retroactively perfused with Tyrode Solution (137 mM NaCl, 5.4 mM KCl, 1.2 mM MgCl 2 , 10 mM HEPES, 10 mM glucose, 1.2 mM NaH 2 PO 4 , and 1.2 mM CaCl 2 ) aerated with a mixture of O 2 (95%) and CO 2 (5%) in order to maintain O 2 levels at 800 nmol/mL using a murine Langendorff perfusion apparatus. After a stabilization period of 20 min, the perfusion buffer was switched to the Tyrode Solutions containing various O 2 concentrations (normoxia: 800 nmol/mL; mild hypoxia: 550 nmol/mL; heavy hypoxia: 300 nmol/mL), which have been proven to induce various myocardial injuries in previous studies (Anttila et al, 2017) for an additional 40 min of perfusion. Then, the hearts were cut into small pieces and homogenized in cold isolation buffer (20 mM HEPES, 220 mM mannitol, 68 mM sucrose, 80 mM KCl, 0.5 mM EGTA, 2 mM magnesium acetate, supplemented with protease inhibitors, pH 7.4) for mitochondrial isolation which was done using a protocol adapted from a previous study (McLelland et al, 2016).…”
Section: Isolation Of Mitochondria and Reconstitution Of MDV In Vitromentioning
confidence: 99%
“…Arjamaa suggests that the role of NPs in hypoxia conditions is probably not to counterbalance pressure changes in the circulation, but to regulate oxygen transport causing a contraction of blood volume (diuresis, natriuresis, vascular permeability) leading to hemoconcentration and increased oxygen transport capacity per unit volume of blood [78]. In addition, Anttila et al [79] showed in a Langendorff rat beating-heart device that the BNP level of the infusate increases when the oxygen pressure of the infused solution decreases. The effect of oxygen was independent of the degree of mechanical stretching of the myocardium, even after the heart rate decreased while the pressure conditions remained constant.…”
Section: Pathophysiology Of Cardiac Natriuretic Peptidesmentioning
confidence: 99%
“…Arjamaa suggests that the role of the natriuretic peptide system in hypoxia conditions is perhaps not to counterbalance pressure changes in circulation, but to regulate oxygen transport, by causing volume contraction (diuresis, natriuresis, and plasma shift) leading to hemoconcentration and increasing oxygen‐carrying capacity per unit volume of blood . Furthermore, Anttila et al . have shown in a spontaneously beating Langendorff rat heart, that the BNP level of perfusate is increased when the oxygen tension of the inflowing buffer is decreased.…”
Section: Increased Bnp In Htx Despite Normal Heart Functionsmentioning
confidence: 99%